Defining the core apoptosis pathway in the mosquito disease vector Aedes aegypti: The roles of iap1, ark, dronc, and effector caspases - Liu, Qingzhen (Apoptosis, 2011)
To date, our knowledge of apoptosis regulation in insects comes almost exclusively from the model organism Drosophila melanogaster. In contrast, despite the identification of numerous genes that are presumed to regulate apoptosis in other insects based on sequence homology, little has been done to examine the molecular pathways that regulate apoptosis in other insects, including medically important disease vectors. In D. melanogaster, the core apoptosis pathway consists of the caspase negative regulator DIAP1, IAP antagonists, the initiator caspase Dronc and its activating protein Ark, and the effector caspase DrICE. Here we have studied the functions of several genes from the mosquito disease vector Aedes aegypti that share homology with the core apoptosis genes in D. melanogaster. Silencing of the iap1 gene in the A. aegypti cell line Aag2 caused spontaneous apoptosis, indicating that IAP1 plays a role in cell survival similar to that of DIAP1. Silencing A. aegypti ark or dronc completely inhibited apoptosis triggered by several different apoptotic stimuli. However, individual silencing of the effector caspases CASPS7 or CASPS8, which are the closest relatives to DrICE, only partially inhibited apoptosis, and silencing both CASPS7 and CASPS8 together did not have a significant additional effect. Our results suggest that the core pathway that regulates apoptosis in A. aegypti is similar to that of D. melanogaster, but that more than one effector caspase is involved in apoptosis in A. aegypti. This is interesting in light of the fact that the caspase family has expanded in mosquitoes compared to D. melanogaster.